2005
DOI: 10.1081/lpr-64958
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondriotropic Liposomes

Abstract: Mitochondrial dysfunction contributes to a large variety of human disorders, ranging from neurodegenerative and neuromuscular diseases, obesity, and diabetes to ischemia-reperfusion injury and cancer. Increasing pharmacological efforts toward therapeutic interventions have been made leading to the emergence of "Mitochondrial Medicine" as a new field of biomedical research. The identification of molecular mitochondrial drug targets in combination with the development of methods for selectively delivering biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(56 citation statements)
references
References 28 publications
0
56
0
Order By: Relevance
“…The zeta potentials (−19.58 mV for PEG2-PCL3.8-Br micelles and +12.1 mV for PEG2-PCL3.8-TPPBr micelles) clearly suggested that the TPP cation is located on the surface of PEG2-PCL3.8-TPPBr micelles. 38 The incorporation of CoQ10 into the core of PEG2-PCL-Br and PEG2-PCL-TPPBr micelles increased the micelle hydrodynamic diameter (Table 2). For instance, PEG2-PCL3.8-TPPBr had hydrodynamic diameters of 36.5 ± 3.4 and 44.2 ± 2.7 nm for empty and CoQ10-loaded micelle, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The zeta potentials (−19.58 mV for PEG2-PCL3.8-Br micelles and +12.1 mV for PEG2-PCL3.8-TPPBr micelles) clearly suggested that the TPP cation is located on the surface of PEG2-PCL3.8-TPPBr micelles. 38 The incorporation of CoQ10 into the core of PEG2-PCL-Br and PEG2-PCL-TPPBr micelles increased the micelle hydrodynamic diameter (Table 2). For instance, PEG2-PCL3.8-TPPBr had hydrodynamic diameters of 36.5 ± 3.4 and 44.2 ± 2.7 nm for empty and CoQ10-loaded micelle, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, the CTPP-PE derivative was obtained as a purified lyophilized powder that was dissolved in chloroform to be incorporated in the lipid mixture to prepare CTPP-PE liposomes. As previously characterized by Boddapati [10] and Biswas [11], typically the TPP cation is identified by the presence of signals of the protons corresponding to the aromatic groups at around 7.68 to 7.88 ppm when characterized by …”
Section: Ctpp-pe Synthesis and Characterizationmentioning
confidence: 93%
“…For example, Boddapati conjugated the TPP cation to the stearyl moiety and incorporated the modified STPP cation into liposomes. According to reported data these STPP liposomes efficiently accumulated into mitochondria and delivered drugs such as ceramide or anti-cancer drugs [10]. However, the non-specific toxicity of the TPP cations due to an excessive accumulation of the TPP cations within mitochondria still remained as the main drawback.…”
Section: Influence Of Triphenylphosphonium (Tpp) Cation Hydrophobizatmentioning
confidence: 99%
“…Other technique was the utilization of mitochondriotropic cationic amphiphiles, like triphenyl phosphonium ion (TPP), which utilizes the high membrane potential of the mitochondrial membrane and has been shown to successfully deliver PNA oligomer to the mitochondria after conjugation to TPP [21]. In a less toxic alternative, mitochondriotropic liposome's modified by amphiphilic cations displayed cargo delivery to mitochondria and a promise for gene delivery applications [22]. The liposome's prepared with isolated mitochondrial fraction were also shown to deliver DNA to the mitochondria of mammalian cells [23].…”
Section: Dna Delivery To Mitochondriamentioning
confidence: 99%